On generalized difference Hahn sequence spaces - Kuldip Raj,; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
We construct some generalized difference Hahn sequence spaces by mean of sequence of modulus functions. The topological properties and some inclusion relations of spaces are investigated. Also we compute the dual of these spaces, and some matrix transformations are characterized.